A case of zosteriform Darier's disease with seasonal recurrence - Lalit K Gupta; Anubhav Garg; Ashok Kumar Khare; Asit Mittal (Wolters Kluwer Medknow Publications, 2013)
Darier's disease is an uncommon genodermatosis characterized by keratotic papules in seborrheic distribution. The disease can rarely present in unilateral zosteriform pattern, as a mosaic form following the Blaschko's line. We present a 35-year-old woman with zosteriform pattern of Darier's disease over right infra mammary region. The lesions occurred strictly during summers. Histologically, suprabasal acantholysis with abundant dyskeratotic cells were seen.